Influence Of Emulsifier On The Quality Of Various Extraction Flour Pretzels (Applied Biological Research, 2010)
Studies were carried out to evaluate the effect of extraction rate of flour, viz. 70, 80  and 90%, on proximate composition, rheological and pretzel-making properties.  The study revealed that with increase in extraction rate from 70 to 90%, the ash,  fat, protein, reducing and total sugar contents showed increase; whileas starch and  falling number showed decrease both in flour and pretzels, respectively. Extended extraction rates resulted in coarser flour affecting their rheological properties.  Farinogram characteristics like water absorption, dough development time and  dough stability increased significantly after 80% extraction rate, while the  amylogram characteristics like gelatinization temperature, peak viscosity, peak  temperature and viscosity at 95oC decreased with extended extraction rate.  Pretzels prepared from different extraction flours exhibited decrease in derived  calories and increase of mineral matter with increase in extraction rate.  Organoleptically, 70 and 80% extraction pretzels were found best with respect to  quality and storage stability. The addition of glycerol momostearate (GMS) at  0.25-0.5% level were suitable for improving texture and storage life of pretzels at  70, 80 and 90% extraction flour pretzels of wheat cv. ‘PBW-343’ but 70 and 80% gave best results. The 70 and 80% extraction flour pretzels had storage life of 90  days.
Keywords: Acceptability; extraction rate; glycerol momostearate; minerals; pretzels; rheological properties; wheat flour